Selections from Mother India - Mayo, Katherine; Sinha, Mrinalini 1960 (New Delhi Kali for Women, 1998)
Includes detailed critical introductory comments by the editor and some comtemporary Indian responses to the "Mother India."
Keywords: Women -- India -- Social conditions; India -- Civilization -- 1765-1947; India -- Social conditions